EFFICIENCY OF ULTRASONOGRAPHY IN DIAGNOSIS OF CHOLECYSTITIS, AND OBSTRUCTED JAUNDICE - Abdulkarim Munif Alotaibi; Abdulrahman Abdulkhaliq Alghamdi; Saeed Nasser Albathan; Fahad Reja Alharbi; Abdulaziz Ali Al Motairi; Mohammed Hlal A Alosimy; Ayman Sulaiman Al Motairi; Raed Humod Alrowily; Rashid Soud Almutiri; Farhan Alhari Alanazi; Awad Saker Almotairi; Ibrahim Mohammed Alyahiwi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Determine the sensitivity and specificity of ultrasonography in diagnosing obstructive jaundice and acute cholecystitis. Using MEDLINE and PUBMED, relevant papers published in English up until June 2022 were systematically searched. Cholestasis, choledocholithiasis, cholangiography, endoscopic, and obstructive jaundice were included in the search approach. Ultrasonography is a trustworthy imaging tool for determining the etiology and severity of blockage in postoperative jaundice. The sensitivity is sufficient to provide early surgical intervention, hence avoiding morbidity and mortality associated with late operations.